A study on water quality of Hail haor ecosystem of Bangladesh - Uddin, MJ; Rahman, Arafat; Zaman, Md Ovi Uz; Rahman, Sharmin; Md Nurnabi, -; Adhikary, Keshab K (Journal of the Asiatic Society of Bangladesh, Science, 2021)
Abstract not available J. Asiat. Soc. Bangladesh, Sci. 47(1): 91-97, June 2021